Fabrication and characterization of a CMOS-MEMS humidity sensor - Dennis, J.-O. (MDPI AG, 2015)
This paper reports on the fabrication and characterization of a Complementary Metal Oxide Semiconductor-Microelectromechanical System (CMOS-MEMS) device with embedded microheater operated at relatively elevated temperatures (40 °C to 80 °C) for the purpose of relative humidity measurement. The sensing principle is based on the change in amplitude of the device due to adsorption or desorption of humidity on the active material layer of titanium dioxide (TiO2) nanoparticles deposited on the moving plate, which results in changes in the mass of the device. The sensor has been designed and fabricated through a standard 0.35 µm CMOS process technology and post-CMOS micromachining technique has been successfully implemented to release the MEMS structures. The sensor is operated in the dynamic mode using electrothermal actuation and the output signal measured using a piezoresistive (PZR) sensor connected in a Wheatstone bridge circuit. The output voltage of the humidity sensor increases from 0.585 mV to 30.580 mV as the humidity increases from 35 RH to 95 RH. The output voltage is found to be linear from 0.585 mV to 3.250 mV as the humidity increased from 35 RH to 60 RH, with sensitivity of 0.107 mV/ RH; and again linear from 3.250 mV to 30.580 mV as the humidity level increases from 60 RH to 95 RH, with higher sensitivity of 0.781 mV/ RH. On the other hand, the sensitivity of the humidity sensor increases linearly from 0.102 mV/ RH to 0.501 mV/ RH with increase in the temperature from 40 °C to 80 °C and a maximum hysteresis of 0.87 RH is found at a relative humidity of 80. The sensitivity is also frequency dependent, increasing from 0.500 mV/ RH at 2 Hz to reach a maximum value of 1.634 mV/ RH at a frequency of 12 Hz, then decreasing to 1.110 mV/ RH at a frequency of 20 Hz. Finally, the CMOS-MEMS humidity sensor showed comparable response, recovery, and repeatability of measurements in three cycles as compared to a standard sensor that directly measures humidity in RH. © 2015 by the authors; licensee MDPI, Basel, Switzerland.